2015
DOI: 10.1249/mss.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Physical Self-concept and Participation in Physical Activity in College Students

Abstract: These results suggest that strategies that contribute to reinforce PSC are primordial and should be targeted as key components for designing effective PA behavior change interventions among college students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 26 publications
0
23
1
8
Order By: Relevance
“…The results of the present study showed that this approach directly affected academic effort and led to an improvement in academic self-concept in students. Previous research has indicated that self-concept is one of the important factors which plays key role in students' success in various courses, including math (21) and many of the adolescents' physical and motor behaviors can be altered via physical self-concept (22). Additionally, selfconcept is among predictors of aggression among students (23).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study showed that this approach directly affected academic effort and led to an improvement in academic self-concept in students. Previous research has indicated that self-concept is one of the important factors which plays key role in students' success in various courses, including math (21) and many of the adolescents' physical and motor behaviors can be altered via physical self-concept (22). Additionally, selfconcept is among predictors of aggression among students (23).…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that physical exercise will produce various physiological benefits such as the improvement of cardiac output, the exchange of pulmonary gases or muscle capillarization, which will increase the maximum oxygen consumption [13,19,20]. Moreover, PA will also improve body composition, which will directly affect the physical dimension of self-concept [26,64]. It should be noted that MD was not related to VO 2MAX , which could be justified by the greater dependence of this indicator on sport habits and training intensity parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this model, numerous studies have found that among children and adolescents a positive self-concept for PA predicts future exercise behavior [36, 37], with some studies finding longitudinal effects spanning across 13 years [38]. Similarly, among young adults, those with a positive self-concept for a particular activity (e.g., aerobic exercise) are more likely to engage in that specific activity [39]. However, predictors of PA among adolescents and younger adults may differ from those of older adults.…”
Section: Introductionmentioning
confidence: 88%